1977
DOI: 10.1002/aja.1001490105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of pericytes in mouse heart

Abstract: The pericytes of mouse myocardium are extensively branched cells that form an incomplete layer around the endothelium of capillaries and postcapillary venules. The membranes of pericytes and endothelial cells are connected by specialized junctions. Microtubules, intermediate (10-nm) filaments and microfilaments are oriented within circumferentially-arranged cytoplasmic processes of pericytes so as partially to encircle the endothelial cylinder. The intracellular organization of these myocardial pericytes sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
16
0
1

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 45 publications
4
16
0
1
Order By: Relevance
“…Actin has already been identified in pericytes (12,14,21,35), and, in the companion paper, we present evidence for the presence in these cells of myosin in relatively high concentration (18).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Actin has already been identified in pericytes (12,14,21,35), and, in the companion paper, we present evidence for the presence in these cells of myosin in relatively high concentration (18).…”
supporting
confidence: 70%
“…Pericytes can be distinguished from other perivascular cells, such as adventitial fibroblasts, by their location within the basement membrane of the vessels, and by the close apposition of the tips of their processes to the underlying endothelium. Electron microscopic studies have identified pericytes in a number of tissues and organs (I0, 12,20,36). They may, in fact, be common to all microvascular beds, although their relative frequency and distribution appear to vary from one microvascular bed to another (32,33).…”
mentioning
confidence: 99%
“…The controversy persisted until STENSAAS (1975), using a modified Golgi staining, put forward convincing evidence that the configuration of the pericyte as originally proposed by ZIMMERMANN was actually the case for most microvessels. The pericytic diagram proposed by FORBES et al (1977) organs and tissues examined in this study, it appeared that the number of capillary pericytes is positively related to the density of the capillary bed. More numerous pericytes occurred at capillary bifurcations than elsewhere, as described by MURAKAMI et al (1979).…”
Section: Discussionmentioning
confidence: 98%
“…Pericytes have properties of smooth muscle cells and are involved in control of the blood flow through microvasculature [45][46][47]. It has been repeatedly shown that administration of LH/hCG promptly (within 2 min) and specifically increases blood flow to the nonluteal portion of the ovary [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%